Microscopy Conference 2009 Graz, Austria 30 Ogos - 04 September 2009 - Ghazali, Farid Che (2009)
Malaysia is blessed with natural products that represent a valuable source of bioactive agents with potent and unique medicinal properties. However, many of these natural products (marine or herbal) are not strictly phannaceutical products (real medicines) but represent a novel class of dietary supplements or nutriceuticals or exploited in traditional medicines. Traditional medicines has not only been used for primary health care of the poor in developing countries but has also been used in countries where conventional medicines are predominant. This have causes commercial exploitation that has endangered species of therapeutic natural products. In order to claritY and ascertain the identities and properties of the species, effort by utilizing high-resolution electron microscopy is now being pursed as a prelude and to harness the taxonomical identity and chemical characterization of therapeutic potentials of these natural products. 'Sanggul F atimah ' or Anastatica Hierochuntica L. (The True Rose Of Jericho), a resurrection plant, is a very well-known traditional herbal remedy closely associated with and consumed minutes prior to labor. This is a rhetoric practice among the Malay Kelantanese women where its tea is believed to help ease childbirth. In the course of our research interest in identi:fYing the most sort herbal during pregnancy and post-partum in Malaysia, we have include a surface morphological characterization of Anastatica Hierochuntica L that was observed under the variable pressure scanning electron microscope (VPSEM). Scanning electron microscopical characterization of this plant is virtually a research lacuna. Information on this herb of the Negev and Sahara Desert is important, as it will affect for the women's attitudes and practices. Results and discussion The supra variable pressure scanning electron microscope study of these plants that dies and dries up, curling its stems into a tight ball revealed a surface characterization built-up of pebbles-like structures, asinu8 rings with thick tunica, an overwhelming soft lamellated surface and spiky coral-like or tom-like structures closely associated with the raised pedunculated putative shoots of cactus-like feature highly prominent in the stem. Microdiffiaction analysis (EDX) of the herb revealed inert significant presence of carbon, oxygen, silica, calcium, magnesium, aluminum, potassium, zinc and iron. Although silica is quite significant in major probe areas, the topographical distributions of these periodic elements are non-homogenous. The combination silica and calcium may be associated with bones repairs and help form collagen. This suggests that the folkloric use of Anastatica Hierochuntica L. in labor and post labor will enhance good tissue and organ repair. The microdiffiaction analysis also suggest therapeutic potential role as a adjuvant supplement in the improvement in bone density and in the prevention of osteoporosis.